Maximum Industrial Price: instrument for pricing negotiation and regulation of high-cost medicines in Chile - Poblete, Sergio (Revista Chilena de Salud Pública, 2022)
The Financial Protection System for Diagnostics and High-Cost Treatments established the Maximum Industrial Price in Chile, which is defined as the maximum price to be paid for a technology that is part of this regime. The Maximum Industrial Price is determined in the evaluation process and three ele¬ments are considered: external reference pricing, internal reference pricing and the supplier offers. In most cases, the supply offer is the source that prevails, because it is the lowest value. On this stage, Maximum Industrial Price works in the context of a price negotiation. Once the medicine is incorporate into guarantees, Industrial Maximum Price works as a price cap for most of medicines that hold their single supplier condition. In the case of drugs that get new suppliers, the Maximum Industrial Price is no longer an active regulation mechanism since the actual purchase prices are far below the ceiling price. The main recommendation to improve the Industrial Maximum Price is to assume a more dynamic approach in its determination with multiple rounds of negotiation and with updating criteria defined a priori, for which it is necessary to develop an institutional framework for the negotiation of prices in the public health system.